2020
DOI: 10.21203/rs.3.rs-36113/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of WRKY Gene Family in Camelina Sativa

Abstract: Abstract Background: WRKY gene family is one of the largest transcription factor families and WRKY proteins (WRKYs) have the complex biological functions to regulate plant metabolic processes. Although the WRKY genes were identified in many species and the functions were verified, there were no reports of Camelina sativa WRKY genes.Results: In this investigation, a total of 202 CsWRKY genes were id… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(78 reference statements)
2
1
0
Order By: Relevance
“…2). This was consistent with that the WRKYGKK variant was frequently occurred in Group IIc of plant WRKY genes [4,7,9,55,[57][58][59]. It has been showed that variation of the WRKYGQK core sequence might affect the binding ability of the WRKY transcription factor to the W-box motif [60,61].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2). This was consistent with that the WRKYGKK variant was frequently occurred in Group IIc of plant WRKY genes [4,7,9,55,[57][58][59]. It has been showed that variation of the WRKYGQK core sequence might affect the binding ability of the WRKY transcription factor to the W-box motif [60,61].…”
Section: Discussionsupporting
confidence: 88%
“…1). This was similar to many other dicot plant species [6,7,9,11,55,56], suggesting that this subgroup was more active in the evolution of dicots. The WRKYGQK core sequence is a typical signature of WRKY proteins.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation